"A Single Woman … Among So Many Men": Negotiating Gendered Spaces in John Gregory Brown's Audubon's Watch. (August 2013) - MICHAILIDOU, ARTEMIS
<x content-type="archive" xml:space="preserve">Abstract</x> This paper examines the notion of gendered space in Audubon's Watch, the most recent work by New Orleans novelist John Gregory Brown. Focussing on Myra Richardson Gautreaux – perhaps Brown's most intriguing female protagonist – it explores, first, how Myra continuously employs "forbidden" language in order to problematize subjects like physical intimacy and sexual desire and, second, how her linguistic experimentation, combined with her solitary walks through the dark streets of nineteenth-century New Orleans, disrupts the dichotomy of public versus private. It also argues that Myra's consistent preoccupation with disciplines inaccessible to nineteenth-century women – like anatomy, the depiction of bodily functions in painting, or the importance of the artist's gaze – establishes a new notion of identity, which interrogates the acceptable limits of "the feminine" in the antebellum South. Ultimately, the paper shows that Audubon's Watch should be read not only as an interesting hybrid of southern gothic and fictional biography, but also as a multilayered work that attempts to redefine the gendered spaces of language, science, and art.